2020
DOI: 10.3390/app10010338
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid End-to-End Approach Integrating Conditional Random Fields into CNNs for Prostate Cancer Detection on MRI

Abstract: Prostate Cancer (PCa) is the most common oncological disease in Western men. Even though a growing effort has been carried out by the scientific community in recent years, accurate and reliable automated PCa detection methods on multiparametric Magnetic Resonance Imaging (mpMRI) are still a compelling issue. In this work, a Deep Neural Network architecture is developed for the task of classifying clinically significant PCa on non-contrast-enhanced MR images. In particular, we propose the use of Conditional Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…make it evident that the EKG treated signals cannot be described by the classical GRF model in Adler and Taylor [1, p. 294], Eqs. (7,11,14. So, we use our DMEPC method to describe these NGRF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…make it evident that the EKG treated signals cannot be described by the classical GRF model in Adler and Taylor [1, p. 294], Eqs. (7,11,14. So, we use our DMEPC method to describe these NGRF.…”
Section: Resultsmentioning
confidence: 99%
“…Alsiddiky et al [13] observed spine tumors using a hierarchical hidden Markov random field (HHMRF) and deep neural networks. The conditional random fields (CRF) were engaged as a recurrent neural network to detect prostate cancer [14]. Here CRF is intended to capture a probability distribution from images' observations, as described in some works cited in [15].…”
Section: Introductionmentioning
confidence: 99%
“…In future work, we suggest that an automatic segmentation model could be used to provide basic guidance for the expert to produce a larger dataset so that a more robust model can be developed. Furthermore, a combination of Multiparametric MRI (such as T1w, T2w, ADC and PDw) can be considered as input to the neural network model to provide more initial features (i.e., information) for the network to perform the segmentation as it has been shown to be significantly beneficial in prostate segmentation [27,62] and prostate cancer detection [63]. Furthermore, integration of Attention Gates (AGs) [64] and Squeeze-and-Excitation (SE) blocks [65,66] are shown to increase the performance of the U-Net model in performing segmentation [64,66] and could be considered as another component for optimisation in the U-Net structure as performed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Then they plugged the RNNs into CNN and applied this method to the problem of semantic image segmentation, obtaining top results on the VOC dataset. Lapa et al [40] also incorporated CRFs into an end-to-end network for medical image segmentation. In addition, many deep learning methods to enhance feature expression have also been proposed for medical image segmentation.…”
Section: The Methods Based On Deep Learningmentioning
confidence: 99%